Is it time for a new meritocracy?. (July 2022) - Tašner, Veronika; Gaber, Slavko
Meritocracy is a rationality that has significantly shaped the lives of people in modern societies, and today we all more or less believe that those who are smart, capable and hardworking will succeed in life. This seems to be a rule that applies in more or less all areas of public life. In the Western world, evaluating and judging ourselves and others based on meritocracy has become an imperative that we rarely question and despite the problems associated with meritocracy, politicians, parents and teachers continue to promote it. In The Tyranny of Merit: What's Become of the Common Good?, Prof. Sandel lays out the genealogy of the aforementioned prevailing rationality and, in particular, highlights the limits and problems of meritocracy that are often overlooked. However, he does not leave it at a mere critique, but also offers a reflection on ways out of the problems of meritocracy. We continue along the path taken by the professor. The first part of our article highlights the critique as reconsiderations of the concept, then continues with reflections on the future of education, merit and wage labour, and concludes with thoughts on the possibility of creating a new meritocracy.